1993
DOI: 10.1085/jgp.102.1.25
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Na channels of the rat cortical collecting tubule by aldosterone.

Abstract: The activity of apical membrane Na channels in the rat cortical collecting tubule was studied during manipulation of the animals' mineralocorticoid status in vivo using a low-Na diet or the diuretic furosemide. Tubules were isolated and split open to expose the luminal membrane surface. Induction of Na channel activity was studied in cell-attached patches of the split tubules. No activity was observed with control animals on a normal diet. Channel activity could be induced by putting the animals on the low-Na … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
132
3

Year Published

1997
1997
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(162 citation statements)
references
References 27 publications
(35 reference statements)
27
132
3
Order By: Relevance
“…Although this disagrees somehow with previous studies that reported no active ENaC in control Na ϩ -replete rats (18), it is worth noting that the frequency of ENaC remained low and the number of channels per patch was always Յ4. As previously reported (18,19), the frequency of patches with ENaC increased greatly in Na ϩ -depleted rats (12 of 27, 44.4%), and the number of channels per patch was Ͼ4 in two of three of the patches. The situation was intermediate in CCD from PAN-nephrotic rats, with 18.6% of patches (eight of 43) that contained ENaC and 50% of the patches with more than four channels.…”
Section: Electrical Activity Of Enaccontrasting
confidence: 99%
“…Although this disagrees somehow with previous studies that reported no active ENaC in control Na ϩ -replete rats (18), it is worth noting that the frequency of ENaC remained low and the number of channels per patch was always Յ4. As previously reported (18,19), the frequency of patches with ENaC increased greatly in Na ϩ -depleted rats (12 of 27, 44.4%), and the number of channels per patch was Ͼ4 in two of three of the patches. The situation was intermediate in CCD from PAN-nephrotic rats, with 18.6% of patches (eight of 43) that contained ENaC and 50% of the patches with more than four channels.…”
Section: Electrical Activity Of Enaccontrasting
confidence: 99%
“…38 -40 Although NF-B-inducible reporter gene was activated in response to aldosterone concentrations as low as 10 Ϫ10 M in cultured CD cells, enhanced proinflammatory gene expression was observed in response to supraphysiologic concentrations of aldosterone in cultured cells and freshly isolated CCD; however, aldosterone-induced NF-B activation observed in CD cells might be relevant to physiopathologic conditions. Indeed, rats under low-Na diet, which classically exhibit high aldosterone circulating levels, 41 exhibit increased expression levels of several NF-B-induced genes, and hyperaldosteronism is frequently observed in both experimental nephropathies 42 and in human chronic renal failure. 43,44 Results obtained in CCD from rats under low-Na diet and evidence obtained in cultured nonclassical aldosterone-responsive proximal tubular cells 45 or glomerular mesangial cells 12 strongly suggest that aldosterone may induce or enhance tubulointerstitial and glomerular BASIC RESEARCH www.jasn.org inflammation and fibrosis via NF-B activation.…”
Section: Discussionmentioning
confidence: 99%
“…On readdition of the hormone, the P o returned to "normal", that is, long open and closed periods with a mean P o between 0.24 and 0.38; however, it appears that low P o of the epithelial Na ϩ channel is not observed in other situations, and hence other authors only saw the appearance of "new channels" with a P o similar to the preexisting ones (if there were preexisting ones) on treatment of A6 epithelia with aldosterone or rats with low-sodium diet (Pácha et al, 1993;Helman et al, 1998). These latter results support the hypothesis that a population of surface channels is switched from a silent mode to an active one by aldosterone or that intracellular channels are translocated to the cell surface.…”
Section: Multiple Effects Of Aldosterone On Enac Regulationmentioning
confidence: 98%